Design and evaluation of sodium alginate-based hydrogel dressings containing Betula utilis extract for cutaneous wound healing - Ishfaq, Bushra; Khan, Ikram Ullah; Khalid, Syed Haroon; Asghar, Sajid (Frontiers in Bioengineering and Biotechnology, 2023)
Traditional wound dressings have a limited capacity to absorb exudates, are permeable to microbes, and may adhere to wounds, which leads to secondary injuries. Hydrogels are promising alternative dressings to overcome the above challenges. In this study, we developed sodium alginate-based hydrogel films loaded with Betula utilis bark extract. These films were prepared via solvent-casting crosslinking method and evaluated for wound healing activity. Prepared films were 0.05–0.083 mm thick, flexible with folding endurance ranging from 197–203 folds, which indicates good physical properties. Optimized formulations exhibited successful loading of extract in the film matrix without any interaction as confirmed by FTIR. Maximum zone of inhibition against Gram-positive and Gram-negative bacteria was achieved by optimum formulation (B6), i.e., 19 mm and 9 mm, respectively, with > 90% scavenging activity. Furthermore, this optimum formulation (B6) was able to achieve 93% wound contraction in rats. Histograms of the optimized formulation treated group also revealed complete reepithelization of wounds. Conclusively, our extract-loaded hydrogel dressing successfully demonstrated its potential for cutaneous wound healing.